Extraction of Implicit Information in Biosignals - Lu, Weixue; Xia, Ling (Methods of Information in Medicine, 1997)
The first part of this paper explains the meaning of implicit information in biosignals. Image reconstruction from projections and ECG inverse problem are two typical examples. In the second part the limitation of conventional ECG inverse problem study is discussed, that is, the excitation propagation process that was not included in inverse study. In the third part a new approach to ECG inverse problem studies is introduced. To verify the new method, we used this method to localize the ventricular preexcitation site with simulated body surface potentials of WPW syndrome. The experimental results show that the inversely recovered preexcitation sites are in close agreement with the true preexcitation site.
Keywords: Inverse Problem; Virtual Reality; Implicit Information